A short message service for campus wide information delivery / Mohammad Mat Ariffin - Mat Ariffin, Mohammad (2002)
This project is about software development that is based on Short Messaging Service (SMS) system for delivering messages to students with mobile phones. The students' information is held in a database that can be accessed through Graphical User Interface (GUI). This software allows the lecturer to maintain a list of students on each course with their respective mobile phone numbers. Upon selection of a send function, an individual may be sent with results or notices from their lecturer. The steps and ways taken to key in the student information via GUI and also how to send the message using the software are indicated. The software is developed using Visual Basic 6.0 with Query based on Structured Query Language (SQL) and ActiveX Data Object 2.0 Library (ADO). Database is held in Microsoft Access 97. The interface between Simplewire's Wireless Message Protocol servers and an External Messaging Entity is designed. Using this interface, an external entity can submit, cancel, register, check, lookup, and query Simplewire's network. It is done using Simplewire's Wireless Message Protocol (WMP) Software Development Kit (SDK) SDK 2.0 and Simplewire™ ActiveX SMS (SDK) 2.4.2 for Visual Basic.